2007
DOI: 10.2298/jsc0705459p
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial evaluation of some benzimidazole derivatives and their zinc(II) complexes

Abstract: Zinc(II) chloride was reacted with some 1-benzylbenzimidazole derivatives (L) to give complexes of the formula ZnL2Cl2. All the ligands and their zinc(II) complexes were evaluated for their in vitro antibacterial activity against Pseudomonas aeruginosa, Bacillus cereus, Staphylococcus aureus and Sarcina lutea. Themajority of the investigated compounds displayed in vitro antimicrobial activity against very persistent microorganisms. It was found that all the tested compounds were more active against gram-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…Antibacterial activity of 1-benzylbenzimidazole derivatives and their Zn(II) complexes was evaluated. It was found that all the tested compounds were more active against Gram-positive bacteria as compared to activities against Gram-negative bacteria [19]. Antimicrobial activity of Zn(II), Ni(II), Cu(II) and Co(II) complexes of thiabendazole against Escherichia coli, B. subtilis and A. flavues organisms was estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity of 1-benzylbenzimidazole derivatives and their Zn(II) complexes was evaluated. It was found that all the tested compounds were more active against Gram-positive bacteria as compared to activities against Gram-negative bacteria [19]. Antimicrobial activity of Zn(II), Ni(II), Cu(II) and Co(II) complexes of thiabendazole against Escherichia coli, B. subtilis and A. flavues organisms was estimated.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of benzimidazoles has received a lot of attention owing to the varied biological activity exhibited by a number of these compounds. [1][2][3][4][5][6][7] This class of molecules proved to be very important, as they possess pharmaceutical properties, including antibacterial, against different strains of Gram-positive and Gram-negative bacteria, 8-10 antifungal 3 and herbicidal 11 activity. It is also well-known that these molecules are present in a variety of analgesic, 12 anti-oxidant, 13,14 anti-allergic 15,16 and antitumoral 17 agents.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial activities of the free ligands against the same bacteria were tested in a previous study. 8 Minimum inhibitory concentration (MIC) was determined by the agar dilution method according to guidelines established by the NCCLS standard M7-A5. 29 The MIC is described as the lowest concentration of a compound that visibly inhibited the growth of a colony.…”
Section: Antibacterial Investigationsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This class of compounds has been found to show antimicrobial activities against Gram-positive and Gram-negative bacteria, primarily because of the potential bio-activity of benzimidazole--based ligands. [8][9][10] Hence, the incorporation of imidazole and benzimidazole nuclei is an important synthetic strategy in drug discovery.…”
Section: Introductionmentioning
confidence: 99%